Heavy Metal Content in Fish and Shellfish Consumed in Ecuador: A Systematic Review - Enriquez, Miguel (2025)
Heavy metal contamination in fish and shellfish is a critical issue that compromises food safety and human health in Ecuador. Metals such as mercury (Hg), lead (Pb), cadmium (Cd), and arsenic (As) accumulate in aquatic ecosystems through bioaccumulation and biomagnification processes, increasing their concentration along the food chain. The study reveals a concerning bioaccumulation of heavy metals in aquatic species, particularly in Thunnus albacares and Anadara similis, with Hg (9.60 mg/kg) and As (16.99 mg/kg) levels exceeding regulatory limits. The PRISMA review ensured the quality of the analyzed studies, highlighting the impact of contamination in oil-producing areas. The biomagnification of mercury and the capacity of bivalve mollusks as bioindicators underscore the need for environmental monitoring. These findings reinforce the importance of strict regulations to mitigate risks to human health and food safety.